Pengaruh Model Guided Inquiry terhadap Hasil Belajar Biologi - Widhiastuti, Setiasih Rizki; Maridi, Maridi; Suciati, Suciati (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2019)
The aims of this research is to determine the effect of Guided Inquiry model towards Biology learning outcomes This research is quasy experiment with posttest only with non-equivalent control group. Population in this research is all students from 5 class in XI grade MIPA of SMA Negeri 8 Surakarta. Samples of this research was taken by cluster purposive sampling technique with XI MIPA 4 as the control class and XI MIPA 5 as the experiment class, with total participants in this research are 52 students. The experimental class uses Guided Inquiry model, meanwhile the control class uses conventional learning. Techniques of collecting data is using test, documentation, and observation. The research hypothesis test is using independent sample t-test assisted by SPSS 19 program with level of significance 0,05. The results showed that cognitive domain has p-value 0,00 <sig. 0,004 and t-value 3,042> 1,673 t table; p-value affective domain 0,048 <sig. 0,05 and t-value 2,023 > 1,673 t table; p-value psychomotor domain 0,00 <sig. 0,05 and t value 3,617 > 1,673 t table. Class who were learning through Guided Inquiry model, showed average value of learning outcomes is higher, compared to class who were learning through conventional model. The conclusion of this research is there is effect Guided Inquiry model towards Biology learning outcomes.